B-type natriuretic peptide-guided therapy for chronic heart failure reduces all-cause mortality compared with usual care but does not affect all-cause hospitalisation or survival free of hospitalisation. Issue 5 (5th August 2010) - Richards, A Mark
Abstract : Commentary on: Porapakkham P Porapakkham P Zimmet H . B-type natriuretic peptide-guided heart failure therapy: A meta-analysis . Arch Intern Med 2010 ;170 :507 –14 .